Representation of medieval climate fluctuations in Central Asia in the toponymic system: Historical and geographical data - Kulyash Kaimuldinova; Shakhislam Laiskhanov; Duman Aliaskarov; Rakhat Tobajanov; Zhulduz Nizamatdinova (Journal of the Bulgarian Geographical Society)
This article considers the nature of climate changes in the Middle Ages of Central Asia and the influence of these changes on the toponymy in the region. The aim of the study is to analyze the manifestation of climate changes in the names of natural objects described in historical data of Central Asia and to study whether the semantic load of toponyms corresponds to the current geographical reality. The spatial identification of toponyms found in medieval historical sources, their etymological and semantic analysis, determination of the correspondence between toponyms and the present geographical nature of objects are carried out in accordance with the aim of the research. Climate changes will lead to changes in soil, vegetation and fauna. The presence of information describing the natural conditions in the period of their appearance in toponyms makes it possible to use them as indicators of landscape changes in historical geography. It was found that toponyms reflect climate changes in Central Asia, and thus they can be used as a source of information in the reconstruction of landscapes of past periods as a result of the research. It was found that the meaning of historical names preserved in the region from the period called “medieval pluvial” or “medieval climate anomaly” (between 900–1300 AD) does not correspond to the nature of the present landscape as a result of climate changes. The research methodology and results can be used in the future on a wider scale for other regions or in historical-geographical studies related to certain time periods.